Waves, particles, and fields : introducing quantum field theory - Fischer-Cripps, Anthony C. (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2019)
"This book presents a background to the concepts of quantum physics; from its inception and the original quantum physics of the Schrodinger Equation through to modern-day theories. It discusses the basics of mechanics, relativity, old and new quantum theory, and Feynman and the concept of a quantum field. It provides the necessary foundation for readers to then progress to more advanced texts on quantum field theory. This book will be of interest to undergraduate students in physics and mathematics and more advanced students looking for a refresher on the subject"--
Mathematics -- Waves -- Electromagnetic waves -- Kinetic theory of gases -- Quantum theory -- The Bohr atom -- The new quantum theory -- Relativity -- Relativistic quantum mechanics -- Quantum field theories -- Conclusions.
OCLC-licensed vendor bibliographic record.
Keywords: Quantum field theory; SCIENCE / Energy; SCIENCE / Physics / General